A NEW METHOD IN EDUCATION: LEAN. - YALÇIN TILFARLIOĞLU, Filiz (Electronic Turkish Studies)
Lean has been in use, especially in automotive industry and other sectors of the manufacturing industry, healthcare, insurance and legal sectors, but its application in education sector is quite new. Lean is a systematic approach that removes waste from processes and adds value to the procedures. Lean aims to remove all the factors that can be described as the waste of sources in various jobs and purposes by creating value and by creating value and oserving the processes of time, labor, money and other resources. When examined from the educational framework, Lean is an organizational development program that strengthens the performance and job satisfaction of every individual in the education system. Lean adds value to the process by defining and eliminating stages which are not necessary and add no value, or even prevent the work from being done or completed. Schools are more effective in providing their activities and services through maximizing the learning skills of all students and creating an environment of success and satisfaction for all by incorporating a system-wide approach to its constitution. In other words, in the framework of Lean education, in a learning group, students and teachers collaborate as equal participants, taking decisions together for solving classroom problems while learning from each other. The problems encountered in the decision making process are not seen as obstacles for achieving goals, but as opportunities for generating new ideas and innovations. However opportunities are used in order to strengthen and renew the related educational process. Principles such as transparency, cooperation, speed and co-learning are the main building blocks of Lean Method. Lean can be easily applied to the structure of every school, and if implemented with its all components, will create sustainable successfocused, human-centered learning environments at the point of evaluating the academic and social environment through the assessment-evaluation processes. While Lean principles, methods, and related tools are successfully used in the service sector, it has never been thought how aforesaid methods will contribute to education. In education, the greatest contribution that Lean will provide is to make the teaching program be balanced and purified from wastes. In this context, Lean will help to build a balanced curriculum, an effective education and training program and enable students to succeed in learning, by providing increased productivity in every stage of the educational processes. In other words, when Lean is adapted to the field of education, it will bring about an organizational development program which advances every individual of the institutions of education aiming at for increasing individual performance and job satisfaction. Lean will identify, interrogate and challenge the elements that slow down and impede the operation in the educational processes. Schools that aim to implement Lean development program will allow every student to experience success and raise their performance to the highest levels. These benefits gathered from Lean will help the schools perform continuous development and innovation movements that our century demands, so, the main purpose of this study is to lead the way how Lean will be effectively implemented by teachers and students in various education systems.